Does thyroid peroxidase provide an antigenic link between thyroid autoimmunity and breast cancer?. Issue 7 (15th October 2013) - Muller, I.; Giani, C.; Zhang, L.; Grennan‐Jones, F.A.; Fiore, E.; Belardi, V.; Rosellini, V.; Funel, N.; Campani, D.; Giustarini, E.; Lewis, M.D.; Bakhsh, A.D.; et al.
<x xml:space="preserve">Abstract</x> Women with breast cancer (BC) and antithyroid peroxidase (TPO) autoantibodies (TPOAb) have a better prognosis than women lacking TPOAb. Sera from women with TPOAb displayed immunoreactivity to BC tissue by immunofluorescence that was not apparent in women without TPOAb. We hypothesize a BC/thyroid shared antigen that provides a target for humoral or cell‐mediated immune activity; candidates include the sodium/iodide symporter (expressed in thyroid and BC), cross‐reacting epitopes in TPO and lactoperoxidase (LPO) or TPO itself. As the association is with TPOAb, we investigated TPO expression in BC, breast peritumoral tissue (PT), other tissues (tumoral and not) and thyroid as positive control. Transcripts for known and novel TPO isoforms were detected in BC (n = 8) and PT (n = 8) but at approximately 104‐fold lower than in thyroid while in non‐BC tumors (n = 5) they were at the limit of detection. TPO was expressed also in adipose tissue (n = 17), 103‐fold lower than in thyroid. Full length TPO (Mr 105–110 kDa) was detected in Western blots in the majority of examined tissues; preabsorption of the TPO antibody with recombinant TPO (but not LPO) reduced the signal, indicating specificity. The same occurred with some lower molecular weight bands, which could correspond to smaller TPO transcript isoforms, present in all samples. In conclusion, TPO is weakly expressed in BC and other tissues; this could partly explain the high frequency and protective role of TPOAb in BC patients. Further studies will investigate tissue specificity, function and immunogenicity of the novel TPO variants (some BC‐specific) identified.